Sedimentary records of giant landslide-dam breach events in western Sichuan, China - Ma, Junxue; Chen, Jian; Xu, Chong (Frontiers in Earth Science, 2024)
Landslide-dammed lake outburst floods (LLOFs) are common natural disasters in high-mountain regions, posing serious safety threats to residents' livelihoods and properties and causing major damage to engineering facilities. Giant landslides and river damming events commonly occur in the Eastern Tibetan Plateau in southwestern China. Dam failure generate LLOFs that form outburst deposits (ODs). This phenomenon is particularly common in some giant ancient landslide-dammed lakes. This study conducted a detailed investigation of the sedimentary characteristics of large-scale landslide-dammed lake outburst deposits in the Diexi Reach of the Upper Minjiang River and Tangjiashan Reach of the Tongkou River Basin, West Sichuan Plateau, China. Meanwhile, typical evidence of high-energy ODs was recorded. The longitudinal distribution of these ODs is similar to an elongated fan-shaped terrace along the river channel, presenting a distinctive sedimentary disordered-sub-ordered-ordered sequence from upstream to downstream. Several typical units of "sedimentary facies" are developed in the OD profiles, such as boulder units deposited by highenergy outburst flood (OF) events and the gravel and sand units representing pulsating-flow sedimentary environments during the recession stage. The grain size frequency curves are bimodal, and the granularity accumulated curves are upward convex, which reflect that the detrital characteristics of the sediment source area are mainly composed of coarse gravel and boulders. This indicates that the coarse gravel sediment gradually become decreased from upstream to downstream. Moreover, the OD hydrodynamic intensity displays a gradual weakening, and sediment sorting is improved. From upstream to the downsream, the mean particle-size and sorting of the ODs gradually decrease. The skewness become larger, and the kurtosis of the ODs is distributed in all the types. In addition, the different combinations of quartz sand surface microtextures indicate the transformation from high-to low-energy impacts over a short distance, which is controlled by flood hydrodynamics and regime. These sedimentary characteristics of ODs explain the hydrodynamic changes during the propagation of OFs, and are also important records for distinguishing between ODs, and "normal" floods.